The role of education offices in the professional development of educational leaders in general education schools in Al-Makhwa Governorate from the point of view of school principals and their agents - Al Omari, Ahmed Yahya Mohammed (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify the role of the educational offices in achieving the professional development of the educational leaders from the point of view of the principals and deputy school principals in public schools in Al- Makhwa governorate in the fields of communication among educational leaders, training and management of the meetings. The study used the descriptive analytical approach, The sample of the study consisted of all managers and their deputies in the public education schools in the governorate of Al- Makhwa, (148) managers and agents. The results of the study are the following:- The overall degree of responses of managers and deputies to assess the role of education offices in achieving the professional development of educational leaders from principals and deputies in public education schools through supervisory practices for school principals and supervisors with an average of (3.21 of 5) which is " medium" degree.- The field of communication was ranked first with an average of (3.41) which is " high" degree. The meeting management area was ranked second with an average of (3.15) and which is " medium" degree. In third place was the field of training with an average of (3.07) which is " medium" degree.
Keywords: professional development; educational leaders; communication; meeting management; training; coordinating supervisor; managers; agents